Potato starch-based biocomposites with enhanced thermal, mechanical and barrier properties comprising water-resistant electrospun poly (vinyl alcohol) fibers and yerba mate extract. (1st July 2019) - López-Córdoba, Alex; Estevez-Areco, Santiago; Goyanes, Silvia
Graphical abstract: Highlights: Electrospun PVA mats were able to act as a reinforcement of starch biocomposites. Starch composites exhibited better light barrier properties than neat starch films. PVA mats and the yerba mate extract increase the elastic modulus of the composites. The new biocomposites showed suitable free radical scavenging activity. Abstract: Water-resistant electrospun poly(vinyl alcohol) (PVA) mats and a yerba mate extract (YM) were incorporated together within potato starch (PS) matrices to prepare biocomposites (PS-YM/PVA/PS-YM). The thermal, mechanical and barrier properties of the PS-YM/PVA/PS-YM systems were compared with biocomposites without YM (PS/PVA/PS) and, with potato starch films without (PS) and with (PS-YM) the YM extract. Scanning electron microscopy analysis showed that the electrospun mats were fully incorporated into the biocomposites and that the PS/PVA interlayer adhesion was only slightly affected by the addition of the extract. Infrared spectra analysis confirmed that this behavior was due to the lower amount of hydroxyl groups available in the biocomposites. As compared with the other systems, the PS-YM/PVA/PS-YM biocomposites exhibited better light- and water vapor barrier properties. Moreover, the presence of the electrospun PVA core layer and the YM extract caused an increase of around 60% in the elastic modulus of these materials.